Development of microwave-multiplexed superconductive detectors for the HOLMES experiment. Issue 6 (May 2016) - Giachero, A; Becker, D; Bennett, D A; Faverzani, M; Ferri, E; Fowler, J W; Gard, J D; Hays-Wehle, J P; Hilton, G C; Maino, M; Mates, J A B; Puiu, A; et al.
Abstract: In recent years, the progress on low temperature detector technologies has allowed design of large scale experiments aiming at pushing down the sensitivity on the neutrino mass below 1 eV. Even with outstanding performances in both energy (~eV on keV) and time resolution (~ 1 μ s) on the single channel, a large number of detectors working in parallel is required to reach a sub-eV sensitivity. HOLMES is a new experiment to directly measure the neutrino mass with a sensitivity as low as 2eV. HOLMES will perform a calorimetric measurement of the energy released in the electron capture (EC) decay of 163 Ho. In its final configuration, HOLMES will deploy 1000 detectors of low temperature microcalorimeters with implanted 163 Ho nuclei. The baseline sensors for HOLMES are Mo/Cu TESs (Transition Edge Sensors) on SiNx membrane with gold absorbers. The readout is based on the use of rf-SQUIDs as input devices with flux ramp modulation for linearization purposes; the rf-SQUID is then coupled to a superconducting lambda/4-wave resonator in the GHz range, and the modulated signal is finally read out using the homodyne technique. The TES detectors have been designed with the aim of achieving an energy resolution of a few eV at the spectrum endpoint and a time resolution of a few micro-seconds, in order to minimize pile-up artifacts.